Culture learning in Myanmar EFL context - Kyaw Sein (Journal of Green Learning, 2022)
In this era of information and technology explosion, peoples in the world encounter one another more often and more easily than ever before. The need for mastering a foreign or second language besides one’s own seems to dramatically grow. More people are learning languages for their personal and professional needs. Specifically, cultural features of the language being learned must be taught concurrently with the linguistic parts, which have traditionally been underlined. Consequently, the present study sought to shed some light on the place of culture in EFL classrooms at educational context in general, and the main goals of teaching culture, major means of teaching culture and the main obstacles facing teachers in teaching culture. To do so, questionnaires were distributed among EFL teachers from different universities and responses were then collected. The findings revealed a gap between the teachers' perceptions and practices in dealing with culture. The data were collected through a questionnaire with 52 Myanmar teachers of English and 86 Myanmar university learners Finally, data analyzed showed that the teachers and learners had positive attitude towards the culture and culture learning. They all preferred to the intercultural communicative competence. And the teachers and learners are actively involved in cultural activities in language classrooms and had the positive attitudes to the cultural activities.